2006
DOI: 10.1007/s10616-006-9005-8
|View full text |Cite
|
Sign up to set email alerts
|

Reactor Engineering in Large Scale Animal Cell Culture

Abstract: This article mainly addresses the issues associated with the engineering of large-scale free suspension culture in agitated bioreactors >10,000 L because they have become the system of choice industrially. It is particularly concerned with problems that become increasingly important as the scale increases. However, very few papers have been written that are actually based on such large-scale studies and the few that do rarely address any of the issues quantitatively. Hence, it is necessary very often to extrap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
311
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 363 publications
(335 citation statements)
references
References 54 publications
10
311
1
1
Order By: Relevance
“…Similar insensitivities to mechanical agitation under aerobic conditions using these experimental and analytical tools have recently been shown for E. coli (Hewitt et al 1998) and Corynebacterium glutamicum (Chamsartra et al 2005). Even animal cells, which do not have a cell wall, are now recognized as being more robust than it was first thought and many such cell lines have been shown to be able to be agitated at T  values up to 0.25 W/kg without a reduction in cell viability or productivity (Nienow 2006). positioned throughout the fermenter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar insensitivities to mechanical agitation under aerobic conditions using these experimental and analytical tools have recently been shown for E. coli (Hewitt et al 1998) and Corynebacterium glutamicum (Chamsartra et al 2005). Even animal cells, which do not have a cell wall, are now recognized as being more robust than it was first thought and many such cell lines have been shown to be able to be agitated at T  values up to 0.25 W/kg without a reduction in cell viability or productivity (Nienow 2006). positioned throughout the fermenter.…”
Section: Discussionmentioning
confidence: 99%
“…However, even animal cells, which were initially thought to be very sensitive to such forces because of the lack of a cell wall (Cherry & Papoutsakis, 1986) have been shown to tolerate relatively high mechanical stresses due to turbulent flow in a stirred bioreactor with mean specific energy dissipation rates, T  up to 0.25 W/kg (Nienow, 2006). On the other hand, because the fluid mechanical stresses associated with bubbles bursting at the surface of the media have local specific energy dissipation rates, T  (W/kg) two to three orders of magnitude higher than those found under typical agitation conditions (Boulton-Stone & Blake 1993), the stresses arising can damage such cells.…”
Section: Impact Of Fluid Mechanical Stress Due To Agitation and Burstmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the only significant effect on the growth or viability of the cells comes from bubble bursting. But, these damages may be strongly reduced by adding a surfactant such as Pluronic F-68, for instance ( Nienow, 2006). The shear rate due to the liquid phase velocity field also takes several forms.…”
Section: Introductionmentioning
confidence: 99%
“…Noteworthy, similar results were found by Gelves [10] who analyzed CFD simulations of a Rushton turbine. The different liquid velocity contours are also checked by the analysis of Kolmogorov length scale [15]:…”
Section: Resultsmentioning
confidence: 99%